Strategi Pembelajaran Qira’ah Untuk Meningkatkan Motivasi Belajar Siswa - Vilda Zahrotul Khoiriyatin; Taufik Siraj (Jurnal Pendidikan Transformatif, 2024)
Arabic language learning is a foreign language learning that is considered difficult by most students, even though Arabic learning is actually easy. A lesson definitely requires the use of effective strategies to increase student motivation and also so that students do not feel difficulties in learning. Arabic learning strategies are carried out so that students can receive more effective and efficient material. The selection of strategies must be based on the language skills taught to students. This type of research uses qualitative research using library research methods because this research is descriptive and uses analysis. This research discusses strategies that can be applied in the learning process of qira'ah to increase student motivation. In this study it was found that effective strategies to increase student motivation such as empety outline, analysis, snow bolling, broken square/texts, and index card match. All of these strategies can be used as a reference for teachers to apply to students so that students are more enthusiastic in learning Arabic, especially in reading skills.